2019
DOI: 10.1002/ps.5641
|View full text |Cite
|
Sign up to set email alerts
|

Primary screening and application of repellent plant volatiles to control tea leafhopper, Empoasca onukii Matsuda

Abstract: BACKGROUND The tea leafhopper, Empoasca onukii Matsuda (Hemiptera: Cicadellidae), is a major pest of tea plants in China. Here, we evaluated the repellent properties of eight volatile chemicals alone and in various combinations as tools for the management of this pest in tea gardens. These chemicals were from the Alliaceae and other aromatic plants, and are known to repel various insect species. RESULTS Among the eight volatile compounds, dimethyl disulfide (DMDS), 1,8‐cineole and allyl methyl sulfide were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The results of the net room trails were used to test the repellent effect of the slow-release blend-2 in the field as previously described with a few modifications. 33 The experiment was conducted in the field from July to October 2020. The DBM population density and number of eggs were confirmed before the field trial.…”
Section: ■ Methods and Materialsmentioning
confidence: 99%
“…The results of the net room trails were used to test the repellent effect of the slow-release blend-2 in the field as previously described with a few modifications. 33 The experiment was conducted in the field from July to October 2020. The DBM population density and number of eggs were confirmed before the field trial.…”
Section: ■ Methods and Materialsmentioning
confidence: 99%
“…The accumulating evidence on the C6-volatile (Z)-3hexenol supports its crucial role in mediating indirect defense responses in plants. Tea The application of plant-derived semiochemicals to control tea pests has been widely reported, such as the application of a mixture of dimethyl disul de (DMDS) and 1,8-eucalyptin to repel E. onukii in tea elds and the application of (E)-2-hexenal, (Z)-3-hexenol, (Z)-hexenyl acetate, (E)-ocimene, linalool, and geraniol as E. onukii attractants (Chen et al 2019;Cai et al 2020). Field trials had shown a signi cant improvement in trapping e ciency when combined with yellow sticky traps.…”
Section: Discussionmentioning
confidence: 99%
“…Some speci c compounds have been successfully used for population monitoring and integrated pest management (Li et al 2014;Chen et al 2019; Wang et al 2020). A binary repellent containing DMDS and 1,8-cineole, for instance, applied by a slow-release method against Empoasca onukii in a tea plantation (Cai et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The volatile compounds were dissolved in liquid paraffin (1%), and 20 µL of solution or paraffin alone was applied to a filter paper square (1 × 1 cm). One arm of the olfactometer [6,9] received a filter paper with the sample and the other arm received paraffin only. Charcoal and humidified, filtered air was driven into each tube with a vacuum pump.…”
Section: Y-tube Olfactometer Testmentioning
confidence: 99%